A hybrid description and evaluation of oxymethylene dimethyl ethers synthesis based on the endothermic dehydrogenation of methanol. Issue 5 (23rd July 2018) - Ouda, Mohamed; Mantei, Franz; Hesterwerth, Kai; Bargiacchi, Eleonora; Klein, Harald; White, Robin J.
Abstract : Concerning oxymethylene dimethyl ethers (OME), this work utilises a hybrid process model based on methanol (MeOH) and its partially selective conversion to anhydrous formaldehyde (FA), which in turn is used as the feed for OME synthesis. Abstract : Concerning oxymethylene dimethyl ethers ( e.g. a class of potential oxygenated diesel substitutes; denoted as OME), this work utilises a hybrid process model based on methanol (MeOH) and its partially selective conversion to anhydrous formaldehyde (FA, target MeOH conversion ≥67% and target FA selectivity ≥93%), which in turn is used as the feed for OME synthesis. The model couples the merits of algorithms available in the commercial software CHEMCAD® together with self-developed reactor models as implemented through Matlab® and the coupling node implemented in Visual Basic for Applications (VBA) software. This is followed by process heat integration using PinCH 2.0 software. This modelling is complemented by experimental investigations and results concerning the synthesis of the anhydrous FA/MeOH feed through a designed and developed annular counter current reactor, with the use of Na2 CO3 as an inexpensive and sustainable dehydrogenation catalyst. The process material and energy balance of the proposed process have also been used to evaluate the key performance indicators (KPIs). An overall process yield of 80.3% at 71.7% process energy efficiency and production cost of 951 US per ton of OME3–5 at small production capacity (35 kt per annum) demonstrates the technical and the economic potential of the described process.